Menyegarkan Kembali Pemahaman Teori Demokrasi Melalui Pemikiran Hans Kelsen - Thalhah, HM (Unisia, 2012)
A state based on democratic principle, according to Han Kelsen, needs social consensus about the significance of democracy, the works of democracy and the advantages of democracy for their life. A strong democracy comes from the will of people, and intends to achieve common good and advantages. Therefore, democracy must deal with representatives of the will of people. Democracy must mean the availability of freedom of religion, freedom of expression, and freedom of assembly. Democracy involves compromise, that is the settlement of disputes through a norm which does not completely accommodate the interest of one party, nor contravene the interest of another one. Representative principle of Hans Kelsen has been, in fact, oriented to the process of responsibility to voters. This means that democracy in the context of representative requires great responsibility, especially that of moral, to the voters, and not to political parties. Keywords: democracy, representative, responsibility